Recurrent Respiratory Tract Infection in an infant: Early Diagnosis by Clinical and Radiological Pearls - Sarkar, Shatanik; Patra, Chaitali; Pal, Shibani; Pramanik, Arkapriya (Journal of Nepal Paediatric Society, 2021)
Recurrent respiratory tract infections, a cause of concern for both parents and paediatricians, can have various etiologies entitled to different organ systems. Diagnosing the exact cause warrants both clinical acumen and timely investigations. Here, we are reporting an infant with recurrent respiratory tract infections, where adequate clinical examination prompted us to diagnose the extra-respiratory cause with simple investigations.